Sequences locating the 5' ends of the major simian virus 40 late mRNA forms. - Piatak, M (1983)
The 5' sequences of late mRNA specified by several constructed or naturally occurring deletion or duplication mutants of simian virus 40 were examined. The mutants included viruses with various small deletions centered about 25 nucleotides upstream from the major transcription initiation site, as well as viruses containing tandem duplications of a sequence of 50 nucleotides or less embedding the major transcription initiation site. The results show that the sequences 25 to 30 nucleotides upstream from the major initiation site in the position of the TATA box of other polymerase II promoters are not essential for the precise localization of the initiation site of late mRNA. Rather, we deduce that the major late mRNA start site is determined primarily by sequences located very close to the initiation site, and that the relative abundance of the 5' ends with this initiation site is modulated by nearby downstream sequences. Modification of six nucleotides adjacent upstream to the initiation site almost completely prevents the utilization of this site. Various deletions and substitutions of sequences 21 nucleotides or more downstream from the major initiation site causes upstream shifts in the localization of the most abundantly utilized 5' ends. The sequences immediately downstream from the major simian virus 40 initiation sites contain inverted symmetries that could give rise to secondary structures in either single-stranded DNA or RNA; the possibility that these inverted symmetries function in transcription initiation at the level of DNA structure rather than in RNA stabilization is discussed. Finally, we present additional evidence that precursor species with certain 5' termini are selectively spliced to form 19S RNA, whereas other 5' termini are preferred for forming the 16S RNA splice. We discuss the possibility that this is a consequence of the influence of leader structure on downstream splicing events.